2011
DOI: 10.1093/schbul/sbq147
|View full text |Cite
|
Sign up to set email alerts
|

Focal And Global Brain Measurements in Siblings of Patients With Schizophrenia

Abstract: This study did not reveal structural brain abnormalities in nonpsychotic siblings of patients with schizophrenia compared with healthy control subjects using multiple imaging methods. Therefore, the structural brain abnormalities observed in patients with schizophrenia are for the largest part explained by disease-related factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 93 publications
3
29
1
3
Order By: Relevance
“…One important aspect of an endophenotype is that it should be present in unaffected relatives of patients. The present study and previous reports [12][13][14] question the idea that grey matter abnormalities are present in relatives of patients with schizophrenia. However, our ROI analysis did reveal significantly higher grey matter volume in the ACC in siblings of patients with schizophrenia.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…One important aspect of an endophenotype is that it should be present in unaffected relatives of patients. The present study and previous reports [12][13][14] question the idea that grey matter abnormalities are present in relatives of patients with schizophrenia. However, our ROI analysis did reveal significantly higher grey matter volume in the ACC in siblings of patients with schizophrenia.…”
Section: Discussioncontrasting
confidence: 54%
“…The finding of nonsignificant grey matter differences between siblings and controls is in accordance with results of 3 previous large studies on grey matter in relatives of patients with schizophrenia. [12][13][14] This agreement suggests that enhanced genetic risk for schizophrenia might not be related to substantial differences in grey matter. Although large studies have been unable to find grey matter alterations in relatives of patients with schizophrenia, smaller studies with lower thresholds have often reported grey matter differences between relatives and controls, 23,37 which may explain the positive (albeit inconsistent) effects found in previous metaanalyses.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In vivo MR imaging measurements have shown regional differences in cortical thickness (22) and have revealed focal differences in cortical thickness between healthy control subjects and patients with schizophrenia (23,24), Alzheimer disease (25) or autism (26). The ability to distinguish multiple cortical layers might yield more insight into where cortical thinning mainly takes place, be it in the superficial or deep layers or diffuse in all layers.…”
Section: Discussionmentioning
confidence: 99%